IMPROVINGSEVENTHGRADERS’ABILITYOF MTs MANBAULULUMKWANYARINWRITINGPROCEDURE TEXTTHROUGHESTAFETGAME (RETAIN, 2014)
IMPROVINGSEVENTHGRADERS’ABILITYOF MTs MANBAULULUMKWANYARINWRITINGPROCEDURE TEXTTHROUGHESTAFETGAME Nur Fadilah S1- English Education, Language and Art Faculty, Surabaya State University, nurfadilah.annamirah@gmail.com Esti Kurniasih, S.Pd., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya estikurniasih87@yahoo.com Abstrak Menulis merupakan kecakapan yang perlu dipelajari. Akan tetapi, menulis itu tidak mudah (Scott & Ytreberg, 1990). Preliminary study yang telah dilaksanakan menunjukkan bahwa menulis menjadi masalah bagi siswa, apalagi jika siswa diminta menulis dengan menggunakan genera atau tipe tulisan tertentu seperti teks prosedur. Menulis merupakan sebuah proses mencipta, mengorganisasi, menulis, dan mempoles/mengedit (Hague, 2003). Menulis tidak dapat langsung dikuasai oleh siswa tingkat Sekolah Menengah Pertama/SMP. Oleh karena itu, mengajar menulis seharusnya dilakukan dalam atmosfer kelas yang nyaman dan menyenangkan semisal menggunakan permainan. Apalagi, menggunakan permainan dalam proses belajar mengajar dapat membuat kelas menjadi nyaman (Uberman, 1988). Dalam studi ini, proses belajar mengajar dilakukan dengan menggunakan sebuah permainan yang disebut Estafet game/permainan Estafet. Estafet game/permainan Estafet adalah sebuah permainan yang di adopsi dari permainan olahraga. Focus studi ini adalah tentang memperbaiki kemampuan menulis siswa dalam menulis teks prosedur melalui permainan Estafet. Adapun tujuan studi ini adalah untuk mendeskripsikan bagaimana permainan Estafet memperbaiki kemampuan menulis siswa dalam teks prosedur. Pendeskripsian tersebut meliputi: (1) bagaimana pelaksanaan permainan Estafet dalam pengajaran menulis teks prosedur pada siswa kelas 7 MTs Manbaul Ulum Kwanyar, (2) bagaimana hasil menulis siswa kelas 7 MTs Manbaul Ulum Kwanyar dalam pengajaran menulis teks prosedur selama dan setelah pelaksanaan permainan Estafet, dan (3) bagaiman respon siswa kelas 7 MTs Manbaul Ulum Kwanyar dalam pengajaran menulis teks prosedur setelah pelaksanaan permainan Estafet. Dalam menganalisis data, peneliti menggunakan melakukan beberapa proses, yaitu: (1) pendeskripsian dan (2) sense making. Di tingkat pendeskripsian, peneliti mereview data-data yang sudah dikumpulkan sebelumnya. Sedangkan dalam tingkat sense making, peneliti menorganisasi data berdasarkan pertanyaan penelitian. Peneliti menyortir data menjadi data yang relevan dan yang tidak relevan kemudian mengelompokkannya sesuai dengan pertanyaan penelitian. Penelitian dalam studi ini dilakukan dalam 2 siklus. Siklus pertama dilakukan dalam 3 pertemuan. Hasil dari siklus pertama tidak menunjukkan adanya perbaikan sehingga penelitian dilanjutkan dengan siklus ke 2. Siklus ke 2 dilakukan dalam 2 pertemuan. Dan hasil dari siklus ke 2 menunjukkan adanya perbaikan dalam tulisan siswa selama dan setalah pelaksanaan permainan Estafet. Jawaban siswa dalam kuesioner pun mengalami perbaikan. Kata kunci: kemampuan menulis, teks prosedur, permainan estafet, kelas tujuh. Abstract Writing is a skill which is necessary to learn. However, writing is not always easy (Scott & Ytreberg, 1990). Preliminary study which was conducted showed that writing becomes the problem of students, moreover if the writing is based on a specific genre such as procedure text. Writing is a process of creating, organizing, writing, and polishing (Hague, 2003). It cannot easily be mastered by students of Junior High School level. Therefore, teaching writing should be done in an enjoyable atmosphere such as using game. In addition, using game in teaching and learning process can create a relaxing atmosphere in the classroom (Uberman, 1988). In this study the teaching and learning process was done by using a game which is called Estafet Game. Estafet Game is a sport game which is adopted into teaching. This study focuses on improving students’ ability in writing procedure text through Estafet Game. The purpose of this study is to describe how Estafet Game improves students’ ability in writing procedure text. The description includes: (1) how the implementation of Estafet game in teaching writing procedure text to the seventh graders of MTs Manbaul Ulum Kwanyar, (2) how the students’ writing results of procedure text during and after the implementation of Estafet game in teaching writing procedure text to the seventh graders of MTs Manbaul Ulum Kwanyar, and (3) how the students’ responses after the implementation of Estafet game in teaching writing procedure text to the seventh graders of MTs Manbaul Ulum Kwanyar. In the data analysis, the researcher does some processes of analysis, they are: (1) description and (2) sense making. In description stage, the researcher reviewed the data that had been collected before. While in sense making stage, the researcher organized the data based on the research questions. The researcher sorted the data into relevant and irrelevant data for the research and grouped the relevant data based on the research questions. The research was done in two observations. The first observation was done in three meetings. The result of the first observation did not show improvement, so that the study was continued with the second observation. The second observation was done in two meetings. And the result of the second observation showed improvement in students’ writing both during and after the implementation of Estafet Game. It also showed improvement in students’ writing results, and the result of students’ answers in the questionnaire. Keywords: writing ability, procedure text, Estafet Game, seventh graders. INTRODUCTION English is a tool to communicate in oral and written form (Depdiknas, 2004). It is used by more than half of the world population. Because of its importance, English is also studied at schools as students’ preparation to face the global world. Communicating using English can be in the form of oral, and written. Written observation consists of reading and writing while oral observation consists of listening and speaking. From the four skills above, writing is an essential skill to be mastered. Writing is a productive skill in which someone shows his/her thoughts through written words. According to Nunan (2003), writing is the mental work of inventing ideas, thinking about how to express them, and organizing them into statements and paragraph that will be clear to readers. Writing is not only writing something. Writing is a process of creating, organizing, writing, and polishing (Haque, 2002). As Halliday (in Nunan, 1995) says that in the modern world, written language serves a range of functions in people’s life such as for action (for example, public signs, product labels, television and radio guides, bills, menus, telephone directories, ballot papers, computer manuals), for information (for example, newspapers, current affair magazines, advertisements, political pamphlets), and for entertainments (for example, comics strips, fiction books, poetry and drama, newspaper features, and film subtitles). Seeing the importance of writing skill above, it is necessary to learn writing. It is said in the 2006 English Standard Competence that Junior high school students have to master and be able to compose a short functional text, and procedure, and descriptive essays. Related to writing procedure text, the researcher found that students of MTs Manba’ul Ulum Kwanyar got difficulty to compose and write the text. Therefore, the researcher collaborated with the English teacher of the school to overcome the problem by teaching using Estafet Game as a technique in teaching writing. However, teaching English as foreign language in Indonesia is not simple, it is caused by the Indonesian students who do not have similarities between learning English and learning their mother tongue (Scott and Ytreberg, 1990). Therefore, teachers should find out a solution to the problems through getting interesting techniques, such as using game to make students motivated and interested in the lesson during the teaching and learning process. Teaching by using game has been promoted and applied for many years to help students understand the various aspects of languages. As Uberman states that games are highly motivating and they can give shy students more opportunities to express their opinion and feeling (Uberman, 1988). In addition, games provide an opportunity for real communication although within artificially defined limits, and thus constitute a bridge between classroom and the real world (Hardfield, 1990). Thus, suitable games are needed to help teachers in delivering the materials and to encourage students to be active in class such as Estafet game. Estafet game is a game which is adopted from estafet race. The meaning of the word estafet itself is ‘connected to each other’. In this study, estafet game is made as a technique in teaching English. The researcher chose the game as a technique because it is appropriate to be conducted in her research to solve the problems the teacher has in classroom. When the researcher had a school visit to MTs Manba’ul Ulum Kwanyar, she found that students in one classroom were not motivated and interested in learning English. She asked the teacher why the students were not motivated and interested in English class. The teacher said that maybe the students do not like the situation of the classroom in which the teacher only explains the lesson, asks the students to read and answer the questions that follow the passage. The researcher also asked several students in the classroom and she found that most of students were not satisfied and did not really understand the teacher’s explanation about the lesson. Therefore, they were not motivated and interested in the lesson. From the problem above, the researcher has an initiative to conduct a research to solve the problem in the classroom. She suggested the teacher to use Estafet Game during the teaching and learning activity. The game is done by making a group of five or ten students. Then each group should make a rank from the first to the last students in each group. When they are ready for the game, the teacher gives each group a board marker. After that, the teacher counts for the start of the game. The game begins when the teacher blows the whistle. Then the first student in the first line comes forward brings the board marker and writes the sentence he/she has on the whiteboard. After the first student finished, it is continued by the second student and so until the last student. If each member in a group has gotten their turn to write their sentence on the whiteboard, the turn should be given to the first student, then the second and then the next student to write all sentences they have until the sentences are all written on the whiteboard. This work team can create a fun situation in the classroom, so that the students can be motivated and interested in learning English. The researcher expected that by using this game as a technique in teaching writing, students’ writing ability can improve better. Hopefully, this study can help teachers to find more interesting games to be used in class in order that the teaching and learning process does not run monotonously. METHODOLOGY The aim of this study was to report the implementation of Estafet Game in improving students’ ability in writing procedure text, the students’ writing result during and after the implementation of Estafet Game, the students’ responses toward the implementation of Estafet Game in teaching writing procedure text of MTs Manbaul Ulum Kwanyar.In line with the aim of the study above, a classroom action research was used in this study. Since this study belongs toclassroom action research, the researcher should take an action in the classroom which was in the form of teaching. However, because the researcher was not a teacher yet, she collaborated with the teacher of the classroom in conducting her research. Therefore, the researcher only became the observerduring the teaching and learning activities in the class.She conducted the research in two observations which was said in the study as observation, so that, there were two observations in this study. The first observation was done in three meetings, they were on 12th, 20th, and 26th of January while the second observation was done in two meetings, they were on 2nd, and 3rd of February 2014.At the end of the second observation, the researcher found that the students’ writing improved during and after the implementation of Estafet Game. And the students’ answers in the questionnaire also showed improvement so that the research ended at the fifth meeting. The instruments that the researcher used to collect the data were observation check list, field-note, students’ writing task, and questionnaire. Observation check list and field-notes were used as the instruments to answer the first research question. The observation check list is in the form of yes and no answer, while field note was in the form of words and sentences that contained teachers’ and students’ activities in classroom from the beginning until the end of the meeting. During observation, the researcher wrote the descriptive and reflective part of the field note to ease to find the answer of the research question. Writing task was used to answer the second research question. This instrument was in the form of writing which was given at the end of each observation. And the questionnaire was used to answer the third research question.There were eight questions and three to four choices of answers of each question in the questionnaire. It was used to collect the data about the students' responses toward the implementation of Estafet Game in teaching writing procedure text. The questionnaire was given at the end of the observation in order that the students could answer all the questions. After collecting all of the data which were gotten from the observation checklist, field-note, students’ writing task, and the questionnaire, the researcher then analyzed them descriptively. In analyzing the data of this research, the researcher did two stages of analyzing the data namely, description and sense making(Ary, Jacobs, & Sorensen, 2006). RESULTS AND DISCUSSION Results The researcher did the observation in two observations in which there were three meetings of first observation and two meetings of second observation. The first meeting was on January 12th, 20th, and 26th, 2014 while the second observation was on February 2nd, and 3rd, 2014. On the second meeting of first observation and the first meeting of the second observation, the teacher implemented Estafet game in teaching writing procedure text. He implemented the game by asking students to make a group of five to seven students. Since the students’ number was thirty four, there were four groups with seven students and one group with six students. Each student in a group should write a sentence based the given title. Then they should stick their sentence which they wrote on a long piece of paper on the whiteboard. The students stuck the longpiece of paper in the third counting from the teacher. The students who have gotten the turn should move backward to ease the next students in taking their turn writing the sentence until the complete text are all written on the carton. Then the teacher corrected the students’ writing and asked some of the students to write the correct sentence on the blackboard. On the third meeting of the first observation and the second meeting of the second observation, the teacher gave the students writing task and the questionnaire. Discussion This part presented the discussion of the study which included the discussion of the first observation and the discussion of the second observation. The Discussion of the First Observation The meeting of this study was done in five meetings in which three meetings were done in the first observation and two meetings were done in the second observation. In the first observation, the first meeting was used as material explanation because the time was very limited. The class began late.Though it was late, the teacher could explain the material completely to students and the students responded well to teacher’s explanation. Before the teacher explained the material, he gave a printed procedure text to students. The printed material was given in order that the students had an understanding to the lesson they would study and as sample of procedure text. The teacher asked them to read the text then gave them some questions related to the text. After that, the teacher explained the lesson. During the explanation, the students listen to the teacher’s explanation well. They were also very active. It was seen when the teacher gave them several questions related to procedure text in the printed text, most of them raised their hands and tried to answer the questions.Because the lesson was for writing skill, the teacher asked students to write their answers on the blackboard. It was to make students used to writing. The Discussion of the Implementation of Estafet Game in the First Observation The second meeting in the first observation was for implementing Estafet Game. The game was used to create a positive atmosphere in class. As stated by Uberman (1998) in chapter II that games are used to create a relaxing atmosphere in the classroom.Students tended to be tense and clumsy in English class, especially when they were asked to make writing in English. So that using games iseffective since they motivate the students, lower students’ stress, and give chances to use and practice the language (Deesri, 2002).One of the games that was used in the classroom to motivate and give students chances to practice the language was Estafet Game. In fact, Estafet Game is one of the games in athletic competition (Indarto, 2013). However, the researcher adopted it into a game which could be used in teaching and learning process in the classroom.Moreover, Estafet Game has been applied in other field of education, so that the researcher could have more references on how the game was used. Seeing the possibility of Estafet Game that can be used in teaching English, the researcher took it to be used during her study. During the implementation of Estafet Game, students were very enthusiastic. They could have a situation of learning in which they could learn while playing a game that made them felt enjoy and relax during the teaching and learning process. During the implementation of the game, each student was asked to write a sentence based on the given title of procedure text in group. This aimed to make students enjoy the lesson during the teaching and learning process. The implementation of Estafet Game in the first observation was not really successful if it was seen from the result of students’ writing during the implementation of the game. The other thing that influenced the success of the implementation of the game was time management which was needed to implement the game, including the time which was needed by students in building the complete text with their group. The teacher gave evaluation to the result of students’ writing which was done in group during the implementation of the game. And the students were not afraid when the teacher evaluated their writing because the teacher had told them that it was only a game for learning not a game for competition. The Discussion of the Result of Students’ Writing Task in the First Observation And after the implementation of the game, the students were given a writing task. It was given at the third meeting of the observation. This writing task aimed to measure students’ ability in writing procedure text. The students’ writing were measured by five writing components which are proposed by Heaton (1988) – content, organization, vocabulary, language use, and mechanic. Each of these components has criteria which could be used to decide whether students’ writing was excellent or poor. There are four criteria for each component, they are excellent to very good, good to average, fair to poor, and very poor. However, the main point which was measured in this writing was the three criteria which must exist in procedure text, they are goal, materials, and steps. This was based on the problem which the researcher found during the preliminary study that was the students got difficulty in composing and writing procedure text. After the students’ writings were analyzed, the researcher found that their writings were not improved yet. There were several mistakes in students’ writing which pervaded the incomplete generic structure of the procedure text. The procedure text should have the complete generic structure as Anderson (1998) has proposed that the structure of a procedure text should consist of goal, materials, and steps. However, students’ writing in this first observation did not fulfill the structure yet. Besides, the mistake also came from the organization of sentences which were written by the students which were confusing, the vocabulary which was used were mostly and essentially translation from Indonesian into English, language use, and the mechanics which were used in writing the procedure text. The Discussion of the Result of Questionnaire in the First Observation After being given the writing task, the students were also given questionnaire to find out their responses toward the implementation of Estafet Game. However, students’ answers in the questionnaire did not reach the standard minimum that the researcher made, that is eighty. Therefore, the researcher and the teacher were in an agreement to repeat the observation with the second observation. The Discussion of the Second Observation The second Observation was done in two meetings. The first meeting was done on February 2nd, 2014. This meeting was used to implement Estafet Game, since it was not successful yet in supporting students to improve their writing in the first observation. In this observation, students more understood about how to play the game, so that it did not take a long time to give them explanation on how to play the game. Because of that, the teacher could compress the time needed to implement the game. Besides, the students looked more ready than the first observation. It was because the students had known everything that should be done during the game from the first observation. During the game, the result of students’ writing was better than in the previous one. It was shown by the mistake which was less than the first observation. In addition, the result of students’ writing task also showed a better improvement than the previous one. It was also supported by students’ answers in questionnaire that reached the standard minimum 80 for the class average. This questionnaire was used to know students’ responses toward the teaching and learning process during the study. As stated by Harmer (2007) that student’s responses are different students’ reactions in the same class activities and tasks which are given by the teacher. From the results of both students’ writing results and the students’ answers in the questionnaire, it was concluded that Estafet Game was successful in improving students’ ability in writing procedure text. CONCLUSION AND SUGGESTIONS Conclusion Based on the results of the data in the previous chapter, the researcher made a conclusion that the implementation of Estafet Game could improve seventh graders’ ability in writing procedure text. The research was conducted by the researcher and the teacher in classroom in which the teacher taught the students while the researcher took data during the teaching and learning process. The research was conducted in five meetings, three meetings in the first observation and two meetings in the second observation. The result of the first observation did not show improvements both in the result of students’ writing task and the questionnaire. But then in the second observation, the result of students’ writing showed improvement both during and after the implementation of Estafet Game. The students’ answers in the questionnaire also showed better responses than the first observation. From the five of both of the observation, it was shown that the implementation of Estafet Game could make students more interested and motivated in learning English. Therefore, it could be concluded from the finding of the research that using Estafet Game in teaching and learning process in the classroom could make the students’ writing ability improve. Suggestions From result of the data of the research, the researcher made some suggestions related to the study, they are: the teacher should have come on time to the class. In addition, the teacher should pay more attention to situation of teaching learning process which includes the students’ need and interest in learning, the teacher should change his way of teaching once in a while such as using game. Monotonous way of teaching could make students not interested and motivated to the lesson which causes students could not master the skill that becomes the objective of the lesson, for other researchers who will conduct an action research, it is better to be well-prepared in everything which is needed for the research such as media, time preparation, and the instrument for the research. And if the research has been successful, it is not necessary to add another observation of the research. REFERENCES Depdiknas. ( 2006). Standar Isi dan Standar Kompetensi Lulusan: Mata Pelajarn Bahasa Ingggris (SD/MI, SMP/MTs, SMA/MA, MA/MAK). Jakarta: Depdiknas. Agustien, HelenaI.R. The English Curriculum in Nutsell (paper): presented at national seminar. Teaching Esl in Indonesia a reflection. Malang 2 Oktober 2004. Harmer, J. (2007). The Practice of English Language Teaching. England: Pearson Education Limited. Scott, Wendy A and Ytreberg Lisbeth H. (1990). Teaching English to Children. London: Longman Heaton, J. B. (1975). Writing English Language Test.London: Longman McMillan, J. H. (1992). Educational Research: Fundamental for the Consumer. Virginia: Harper Collins Publishers Depdiknas 2004. Kurikulum 2004: Standar Kompetensi Mata Pelajaran Bahasa Inggris Sekolah Menengah Pertama dan Madrasah Tsanawiyah. Jakarta: Balitbang Depdiknas Heaton, J. B. (1988). Writing English Language Tests. New York: Longman Group UK Limited. Aouladomar, Farida, Leila Amgoud, Patrick Saint-Dizier. (2006). On Argumentation in Procedural Texts. http://www.unicaen.fr/poc/ecrire/preprints/preprint0022006.pdf retrieved on December 2013. Gatzke, Lourie. (2003). Procedural Text. http://www.data.tp.ac.id/document/texts (retrived on December 2013) Ary, D., Jacobs, L. C., & Sorensen, C. (2006). Introduction to Research in Education (8th Edition ed.). Belmont: Wadsworth. Hague, A. (2003). The Essential of English. New York: Pearson Inc. Indarto, H. D. (2013). Analisa Lari Estafet Retrieved February 10th, 2014 Scott, W. A., & Ytreberg, L. H. (1990). Teaching English to Children. New York: Longman Group UK Limited. Uberman, A. (1988). The Use of Game for Vocabulary Presentation and Revision (Vol. XXXVI). Forum: 1st January.